2013
DOI: 10.1093/carcin/bgt097
|View full text |Cite
|
Sign up to set email alerts
|

A novel onco-miR-365 induces cutaneous squamous cell carcinoma

Abstract: The expression levels of miR-365 vary in different malignancies. Herein, we found that miR-365 was overexpressed in both cells and clinical specimens of cutaneous squamous cell carcinoma (SCC). We demonstrated that the HaCaTpre-miR-365-2 cell line, which overexpressed miR-365, could induce subcutaneous tumors in vivo. Antagomir-365, an anti-miR-365 oligonucleotide, inhibited cutaneous tumor formation in vivo, along with G1 phase arrest and apoptosis of cancer cells. These findings suggest that miR-365 may act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 33 publications
(32 reference statements)
7
70
0
Order By: Relevance
“…MiR-365 expression has been so far associated to cancer development and its progression (Zhou et al, 2013). The finding that miR-365 may be related to transport-stress confirms what has been recently reported by Ahanda et al (2014), who demonstrated that miR-365 family members are present in plasma and red blood, but not white blood cells, and their expression is modulated by food deprivation stress.…”
Section: Discussionsupporting
confidence: 84%
“…MiR-365 expression has been so far associated to cancer development and its progression (Zhou et al, 2013). The finding that miR-365 may be related to transport-stress confirms what has been recently reported by Ahanda et al (2014), who demonstrated that miR-365 family members are present in plasma and red blood, but not white blood cells, and their expression is modulated by food deprivation stress.…”
Section: Discussionsupporting
confidence: 84%
“…We previously demonstrated that miR-365 has a procarcinogenic role in CSCC by targeting NFIB (Zhou et al, 2013(Zhou et al, , 2014. Thus, CDK6, as a downstream factor, is also affected and , and CDK4 were detected in the CSCC cell lines Tca8113, HSC-1, and A431 and in normal HaCaT cells by qRT-PCR and western blotting.…”
Section: The Mrna and Proteins Levels Of Cdk6 And Cdk4 Are Highly Uprmentioning
confidence: 97%
“…We previously identified microRNA-365 (miR-365) as an oncomiR that is highly expressed in CSCC cells and clinical tumors (Zhou et al, 2013). Further study of this microRNA led to the identification of a downstream target of miR-365, nuclear factor I/B (NFIB) (Zhou et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study confirmed that miR-365 was downregulated in colon cancer tissues, was involved in tumor progression and poor survival, and regulated cancer cell behavior by targeting cyclin D1 and Bcl-2 (16). miR-365 was also overexpressed both in cells and cutaneous squamous cell carcinoma tissues, suggesting that miR-365 may act as an oncogene both in vitro and in vivo (17). Moreover, recent studies indicated that miR-365 was upregulated in breast cancer (18).…”
Section: Introductionmentioning
confidence: 73%